Model Cities for Resilience: Climate-led Initiatives - Didem Gunes Yilmaz (Alanya Hamdullah Emin Paşa Üniversitesi, 2021)
Paris Agreement of December 2015 was the last official initiative led by the United Nations (UN) as the driver of climate change mitigation. Climate change was hence linked with an increase in the occurrence of natural hazards. A variety of initiatives were consequently adopted under different themes such as sustainable cities, climate-friendly development, and low-carbon cities. However, most of the initiatives targeted by global cities with urban areas being the focus in terms of taking action against global warming issues. This is due to the structural and environmental features of cities characterized by being populated, as such, they not only generate a large number of carbon emissions but also happens to be the biggest consumer of natural resources. In turn, they create a microclimate, which contributes to climate change. Masdar City, for example, was designed as the first fully sustainable urban area, which replaced fuel-based energy with electric-based energy. China, as another example, introduced the Sponge Cities action, a method of urban water management to mitigate against flooding. Consequently, architects and urban planners are urged to conform to the proposals that would mitigate global warming. This paper, as a result, examines some of the models that have been internationally adopted and thereafter provide recommendations that can be implemented in large urban areas in Turkey, primarily in Istanbul.